Putaminal Diffusivity Correlates With Disease Progression in Parkinson's Disease: Prospective 6-Year Study. Issue 6 (February 2016) - Chan, Ling-Ling; Ng, Kia-Min; Yeoh, Chooi-Sum; Rumpel, H.; Li, Hui-Hua; Tan, Eng-King
Abstract : Abstract: Diffusion tensor imaging (DTI) is an increasingly used noninvasive imaging tool. However its long-term clinical utility is unclear. Parkinson's disease (PD) is a common neurodegenerative disease. We prospectively examined a cohort of 46 Parkinson's disease (PD) patients who underwent diffusion tensor imaging (DTI) of the brain at baseline and 6 years later on a 1.5 Tesla scanner using a standardized protocol. DTI parameters of mean diffusivity (MD) and fractional anisotrophy (FA) were extracted using regions-of-interest (ROIs) analysis from various brain regions. Compared to the baseline scan, MD increased in all brain regions ( P  < 0.0001). FA increased in the substantia nigra and posterior putamen, but decreased in the frontal white matter ( P  < 0.0001). Linear regression analysis demonstrated that the MD in the anterior putamen increased 11.6 units (95% CI = [4.71, 18.43]) ( P  = 0.0003) for every unit increase of United PD Rating Scale (UPDRS). Our 6-year prospective longitudinal study demonstrated increased diffusivity in all brain regions and that in the anterior putamen correlated with disease progression. Serial diffusion data may be useful as an additional objective in vivo biomarker for motor progression in PD.